Analisis Resiko Investasi Pasar Modal IDX dalam Penggunaan Transaksi Saham Digital Generasi Z Ditinjau dalam Perspektif Ekonomi Islam di Pulau Sumatra - Dean Amri, Ary; Ade Melda; Dinni Afrisca Sari; Maharani Putri; Zahra Muflihah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out 1) What is the Opinion of Generation Z Against the Risk of Trust and Security of the Digital Capital Market on the Island of Sumatra 2) How is Idx Capital Market Investment Viewed in the Perspective of Islamic Economics. This research method uses quantitative research methods. The data sources used in this study are primary data from questionnaires that have been tested for validity and reliability as well as secondary data. Data analysis used simple regression test and multiple regression test using SPSS. The number of samples in this study were 250 respondents from Generation Z who live on the island of Sumatra which were successfully collected by distributing online questionnaires via the Google form with a random sampling technique. The results of this test show that security (X2) is more dominant than the trust factor (X1), however, both trust (X1) and security (X2) have a positive and significant influence on the risk of stock (Y) Generation Z in Sumatra.